A new species of Ampharete (Annelida: Ampharetidae) from the West Shetland shelf (NE Atlantic Ocean), with two updated keys to the species of the genus in North Atlantic waters - Parapar, Julio; Moreira, Juan; Barnich, Ruth (European Journal of Taxonomy, 2019)
Ampharete oculicirrata sp. nov. (Annelida: Ampharetidae) is described from samples collected by the Joint Nature Conservation Committee and Marine Scotland Science, in the West Shetland Shelf NCMPA in the NE Atlantic. This species is characterised by a very small body size, thin and slender paleae, twelve thoracic and eleven abdominal uncinigers, presence of eyes both in the prostomium and the pygidium, the latter provided with a pair of long lateral cirri. The external micro-morphology of the new taxon was studied using scanning electron microscopy and compared with species described or reported from the North Atlantic. Two complementary keys to all species of Ampharete in the area are also provided.